2018
DOI: 10.3382/ps/pex441
|View full text |Cite
|
Sign up to set email alerts
|

Particle size affects short-term preference behavior of brown-egg laying hens fed diets based on corn or barley

Abstract: We studied the influence of particle size of the main cereal of the diet on preference behavior by laying hens. Diets formed a 2 × 5 factorial with 2 main cereals (corn vs. barley) and 5 grinding sizes of the cereal (4, 6, 8, 10, and 12 mm screen). Each treatment was replicated 5 times (10 hens each). After a fasting period of 8 h, hens received their respective experimental diets from 06.00 to 14.00 hours. The geometric mean diameter (GMD) and the geometric standard deviation of the residuals in the feeder we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Feed particle size was greater in the original diets than in the feed residuals that remained in the feeders 24 h after the offer, confirming that pullets have a preference for coarse particles, as shown in previous studies with broilers ( Portella et al, 1988b ; Xu et al, 2015 ) and laying hens ( Portella et al, 1988a ; Safaa et al, 2009 ; Herrera et al, 2018 ). The data reported herein, however, suggest that the preference response observed might be a combination of the predilection of the pullets for coarse particles and the rejection to consume fine particles.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Feed particle size was greater in the original diets than in the feed residuals that remained in the feeders 24 h after the offer, confirming that pullets have a preference for coarse particles, as shown in previous studies with broilers ( Portella et al, 1988b ; Xu et al, 2015 ) and laying hens ( Portella et al, 1988a ; Safaa et al, 2009 ; Herrera et al, 2018 ). The data reported herein, however, suggest that the preference response observed might be a combination of the predilection of the pullets for coarse particles and the rejection to consume fine particles.…”
Section: Discussionsupporting
confidence: 85%
“…The data reported herein, however, suggest that the preference response observed might be a combination of the predilection of the pullets for coarse particles and the rejection to consume fine particles. In fact, the percentage of coarse particles (average of the 4 treatments) decreased from 53.8% in the original feeds to 39.3% in the refusals, whereas the percentage of fine particles increased from 23.0% in the original feeds to 30.6% in the feed refusals, data that suggest that pullets might reject to consume fine particles, as suggested by Herrera et al (2018) in laying hens. In this respect, Portella et al (1988a) reported that hens discriminate against feed particles smaller than 850 µm.…”
Section: Discussionmentioning
confidence: 82%
“…(2008b) , and Herrera et al. (2017 , 2018 ) reported that the increase in EW observed with increases in the level of supplemental fat was independent of the LNL content of the diet. Moreover, Bouvarel et al.…”
Section: Discussionmentioning
confidence: 97%
“…Highly concentrated energy diets, however, are costly and might reduce feed efficiency for egg production, because part of the energy ingested is directed to fat deposition and BW gain ( Perez-Bonilla et al., 2012a ). On the other hand, high energy diets usually contain more linoleic acid ( LNL ) and supplemental fat than low energy diets ( Grobas et al., 2001 ; Safaa et al., 2008b ; Herrera et al., 2018 ) resulting often in an increase in egg size ( Harms and Waldroup, 1963 ; DeGroote, 1972 ; Grobas et al. 1999b ; Wu et al., 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, finely ground diets might reduce voluntary FI (Safaa et al, 2009;Lohmann, 2016;Herrera et al, 2017Herrera et al, , 2018 and therefore, egg size and egg production (Isa Brown, 2009). In the current research, however, the size of the screen used to grind the cereals had little effect on hen production or egg quality traits.…”
Section: Screen Sizementioning
confidence: 99%